A commentary of factors related to player availability and its influence on performance in elite team sports - Celleja-González, J.; Mallo, J.; Cos, F.; Sampaio, J.; Jones, M. T.; Marqués-Jiménez, D.; Mielgo-Ayuso, J.; Freitas, T. T.; Alcaraz, P. E.; Vilamitjana, J.; Ibáñez, S. J.; Cuzzolin, F.; et al. (Frontiers in Sports and Active Living, 2023)
Elite performance and sporting success are often the result of optimal integration and synergy of all components of sports preparedness (i.e., health, technical and tactical skills, bioenergetic and neuromuscular abilities and capacities, anthropometric characteristics, cognition, emotions, creativity, or personality), which evolve because of systematic long-term sports preparation. However, the relative importance of these characteristics varies between individual and team sports. While some individual sports require a high standard of bioenergetic and neuromuscular abilities and capacities, team sports performance is closely related to technical and tactical skills, which may compensate for weakness within the fitness level (1). Nonetheless, successful team sport performances seem to be much more dependent on the interaction among a wide range of factors than on the maximum development of one or two factors in isolation. In team sports, elite performance emerges from the interaction among the individual parts (2) to overcome the opponent during competition.